‘If no one else stands up, you have to’: a story of community participation and water in rural Guatemala - Ana Ruano; Kjerstin Dahlblom; Anna-karin Hurtig; Miguel Sebastián (Taylor & Francis Group, 2011)
Access to water is a right and a social determinant of health that should be provided by the state. However, when it comes to access to water in rural areas, the current trend is for communities to arrange for the service themselves through locally run projects. This article presents a narrative of a single community's process of participation in implementing and running a water project in the village of El Triunfo, Guatemala.Using an ethnographic approach, we conducted a series of interviews with five village leaders, field visits, and participant observations in different meetings and activities of the community. El Triunfo has had a long tradition of community participation, where it has been perceived as an important value. The village has a council of leaders who have worked together in various projects, although water has always been a priority. When it comes to participation, this community has achieved its goals when it collaborated with other stakeholders who provided the expertise and/or the funding needed to carry out a project. At the time of the study, the challenge was to develop a new phase of the water project with the help of other stakeholders and to maintain and sustain the tradition of participation by involving new generations in the process.This narrative focuses on the participation in this village's efforts to implement a water project. We found that community participation has substituted the role of the central and local governments, and that the collaboration between the council and other stakeholders has provided a way for El Triunfo to satisfy some of its demand for water. El Triunfo's case shows that for a participatory scheme to be successful it needs prolonged engagement, continued support, and successful experiences that can help to provide the kind of stable participatory practices that involves community members in a process of empowered decision-making and policy implementation.